(untitled) (Jurnal Teknologi Industri Pertanian, 2022)
Information about a product’s shelf life is essential for the food industry to ensure the safety and quality of the product. Process development is needed if the product’s shelf life is short-lived. This study aimed to increase the shelf life of ginger latte with sterilization at 121oC temperature using an autoclave for 10, 15, and 20 minutes then being hot filled at 90oC. Product sterilized in aluminum foil pouch then transferred to PET plastic bottles with hot fill method. Beforehand, the product characteristics were tested on the organoleptic test, pH, and total dissolved solids before being treated with sterilization and hot fill. The Arrhenius method was used to calculate product shelf life with sensory, pH, and total dissolved solids as parameters. The product shelf life before sterilization and hot filling were 18 days in storage at 10oC. Based on the calculation using the ASLT method Arrhenius model, the product shelf life was 35 days with sterilization at 121oC in 25oC storage temperature. The pH and total dissolved solids on day 28 after sterilization were recorded at 5.33 and 14.5 oBrix for 15 minutes, respectively, and 5.83 and 14.9oBrix for 10 minutes of sterilization, respectively. Keywords: accelerated shelf life study (ASLT), ginger latte, sterilization, shelf life